(untitled) (JED (Jurnal Etika Demokrasi), 2021)
The subject teacher meeting is a forum formed by the government to facilitate collaboration and collaboration of subject teachers in solving various learning problems and being a forum for developing teacher professionalism. This article aims to analyze and describe the collaboration of PPKn teachers in State Junior High School Sawahlunto City, West Sumatra Province, and the problems that occur in it. This research was conducted with a qualitative approach. Respondents were selected from elements of PPKn teachers who were members of the MGMP State Junior High School Sawahlunto City, MGMP administrators, school principals, and the Education Office of Sawahlunto City. Data analysis followed the stages of qualitative data analysis Miles & Huberman; data reduction, data display, and conclusion drawing. The results of the study show: (1) the problem of weak teacher collaboration in MGMP is related to the impact of the non-formal relationship between teachers, which is too dominant but also to the discipline and teachers motivation. (2) The expected impact of the implementation of MGMP PPKn State Junior High School is an increase in teacher competence in implementing learning which in the end also improves student learning outcomes. However, this target has not been fully achieved because the behavior and average learning outcomes of students are still low. (3) There is no specific strategy to increase collaboration between teachers carried out by the management in the MGMP PPKn forum for State Junior High School Sawahlunto City. Musyawarah guru mata pelajaran merupakan wadah yang dibentuk pemerintah untuk memfasilitasi kerjasama dan kolaborasi guru mata pelajaran dalam memecahkan berbagai persoalan pembelajaran sekaligus menjadi wadah pengembangan professionalisme guru. Artikel ini bertujuan untuk menganalisis dan mendeskripsikan kolaborasi guru PPKn SMP Kota Sawahlunto Provinsi Sumatera Barat serta problematika yang terjadi di dalamnya. Penelitian ini dilakukan dengan pendekatan kualitatif. Responden dipilih dari unsur guru PPKn yang menjadi anggota MGMP SMP Negeri Kota Sawahlunto, pengurus MGMP, kepala sekolah, dan Dinas Pendidikan Kota Sawahlunto. Analisis data mengikuti tahapan analisis data kualitatif Miles& Huberman; reduksi data, display data, dan penarikan kesimpulan. Hasil penelitian menunjukkan: (1) Masalah lemahnya kolaborasi guru dalam MGMP tidak hanya berkaitan dengan dampak hubungan nonformal antar guru yang terlalu dominan tetapi juga karena faktor disiplin dan motivasi guru. (2) Dampak yang diharapkan dari pelaksanaan MGMP PPKn SMP Kota Sawahlunto adalah meningkatnya kompetensi guru dalam melaksanakan pembelajaran yang pada sasaran akhirnya juga meningkatkan hasil belajar peserta didik. Namun target ini belum sepenuhnya tercapai karena perilaku dan rata-rata hasil belajar peserta didik masih rendah. (3) Tidak ada strategi khusus yang dilakukan untuk meningkatkan kolaborasi antar guru yang dilakukan pengurus dalam forum MGMP PPKn SMP Kota Sawahlunto.